Strengthening Teacher's Work Ethic in Learning Through Academic Supervision Activities during the COVID-19 Pandemic Period in Sociology and Management Perspectives - Aep Saepuloh; Ahmad Rusdiana (GoAcademica Research & Publishing, 2021)
Teachers have a very strategic role in advancing national education. Therefore, teachers work with a good work ethic. This study aims to analyze how the work ethic of teachers at Madrasah Ibtidaiyah Al-Mishbah Cipadung during the COVID-19 pandemic in learning through academic supervision activities. This research is a collaborative school action research conducted to improve and improve the quality of teachers in terms of learning work ethic, especially during the COVID-19 pandemic. The results of the pre-action research showed an average score of 64.42, while in the first cycle the average score was 77.7, while in the second cycle the average score was 85.86. This means that there is a significant difference between the work ethic of teachers before and after academic supervision is carried out.